Acupuncture Treatment of Neck Pain in Cold Wind Pathogen Syndrome - Semiwati Widjaja, Kwok; Aldo, Alfredo (Rifa'Institute, 2023)
Introduction: Neck pain is one of the health problems that exist in modern society. Neck pain is one of the main musculoskeletal disorders in the adult population, where the prevalence in the world ranges from 16.7% to 75.1%. In Indonesia, every year, around 16.6% of the adult population complains of neck disorders, of which 0.6% start with discomfort in the neck and progress to severe neck pain. Objective: This study aims to provide an in-depth description of the role of acupuncture in specific neck pain cases caused by cold-weather pathogens. Method: The research design used a qualitative approach with a case study type and was conducted in March–AApril 2023. Result and Discussion: The acupuncture points used were Feng Chi (GB 20), Tian Zhu (BL 10), Jianjing (GB 21), Dazhu (BL 11), Extra Xinshe, and Jianzhongshu (SI 15). The results of this study showed that participants felt pain at the beginning on a scale of 8 before changing to a scale of 1 and 5, and the neck and shoulders no longer felt stiff. Conclusion: And the participants can sleep comfortably and are not disturbed by pain because the complaints they feel have improved.